Débat - Simard, Jean-Jacques; Fournier, Marcel; Bélanger, André-J.; Linteau, Paul-André; Harvey, Fernand; Fournier, Marcel; Simard, Jean-Jacques; Fournier, Marcel; Simard, Jean-Jacques; Piotte, Jean-Marc; Fournier, Marcel; Sales, Arnaud; et al. (Recherches sociographiques)

(untitled) (Département de sociologie, Faculté des sciences sociales, Université Laval, 1985)
Débat